The Deep-Sea Microbial Community from the Amazonian Basin Associated with Oil Degradation - Campeão, Mariana E.; Reis, Luciana; Leomil, Luciana; de Oliveira, Louisi; Otsuki, Koko; Gardinali, Piero; Pelz, Oliver; Valle, Rogerio; Thompson, Fabiano L.; Thompson, Cristiane C. (Frontiers in Microbiology, 2017)
One consequence of oil production is the possibility of unplanned accidental oil spills; therefore, it is important to evaluate the potential of indigenous microorganisms (both prokaryotes and eukaryotes) from different oceanic basins to degrade oil. The aim of this study was to characterize the microbial response during the biodegradation process of Brazilian crude oil, both with and without the addition of the dispersant Corexit 9500, using deep-sea water samples from the Amazon equatorial margin basins, Foz do Amazonas and Barreirinhas, in the dark and at low temperatures (4°C). We collected deep-sea samples in the field (about 2570 m below the sea surface), transported the samples back to the laboratory under controlled environmental conditions (5°C in the dark) and subsequently performed two laboratory biodegradation experiments that used metagenomics supported by classical microbiological methods and chemical analysis to elucidate both taxonomic and functional microbial diversity. We also analysed several physical-chemical and biological parameters related to oil biodegradation. The concomitant depletion of dissolved oxygen levels, oil droplet density characteristic to oil biodegradation, and BTEX concentration with an increase in microbial counts revealed that oil can be degraded by the autochthonous deep-sea microbial communities. Indigenous bacteria (e.g., Alteromonadaceae, Colwelliaceae, and Alcanivoracaceae), archaea (e.g., Halobacteraceae, Desulfurococcaceae, and Methanobacteraceae), and eukaryotic microbes (e.g., Microsporidia, Ascomycota and Basidiomycota) from the Amazonian margin deep-sea water were involved in biodegradation of Brazilian crude oil within less than 48-days in both treatments, with and without dispersant, possibly transforming oil into microbial biomass that then fuels the marine food chain.